Assessment of glove integrity across various dental specialties in a dental school setting - Alsaegh, Mohammed Amjed; AlSiraj, Mohammed Farooq; Alsadoon, Ahmed Naji; Soufi, Omar; Mahmoud, Okba; Varma, Sudhir Rama (Frontiers in Oral Health, 2024)
ObjectivesThis study aimed to evaluate the integrity of non-sterile, powder-free latex gloves used by dental students in various dental specialties.Materials and methodsThis cross-sectional study involved dental students from Ajman University who provided gloves during various dental specialty procedures. A total of 177 pairs of latex examination powder-free gloves were included and categorized as follows: 43 pairs (24.3%) were used in operative dentistry, 30 pairs (16.9%) in oral surgery, 28 pairs (15.8%) in endodontics, 24 pairs (13.6%) in periodontics, 21 pairs (11.9%) in pedodontics, 13 pairs (7.3%) in prosthodontics, and 18 pairs (10.2%) as control gloves. After use, glove integrity was assessed with a modified water leak test.ResultsPerforations were identified in 72 cases (40.7%) of gloves, distributed as follows: 22 cases (51.2%) in operative dentistry, 12 cases (40.0%) in oral surgery, 11 cases (39.3%) in endodontics, 11 cases (45.8%) in periodontics, 10 cases (47.6%) in pedodontics, 5 cases (38.5%) in prosthodontics, and 1 case (5.5%) in the control group. There were no statistically significant differences in the loss of glove integrity among different dental specialty procedures (χ2 = 11.899, p = 0.064) or among different glove usage durations (χ2 = 1.732, p = 0.785). However, the location of perforations in the experimental groups was statistically significant (χ2 = 34.427, p < 0.001). The most common locations were the right thumb (n = 18; 13.7%) and the right index finger (n = 17; 13%), with no perforations in the left ring finger and only one perforation in the left little finger (n = 1, 0.08%). There was a statistically significant correlation between the anticipated and actual presence of defects (χ2 = 32.875, p < 0.001).ConclusionsThe study found a high rate of glove perforations during dental procedures by undergraduate students, especially in the right thumb and index finger. To reduce cross-infection risks, strict protocols like double gloving, frequent glove changes, and covering wounds with plaster are recommended.